2019
DOI: 10.1038/s41598-019-43523-w
|View full text |Cite
|
Sign up to set email alerts
|

Mating structure of the blue and red shrimp, Aristeus antennatus (Risso, 1816) characterized by relatedness analysis

Abstract: Understanding life history variation and strategies is crucial for stock assessment and fisheries management due to the direct effects on population dynamics, effective population size, sex-ratios, levels of inbreeding, and relatedness among individuals. Aristeus antennatus (En ─ Blue and red shrimp; Fr ─ Crevette rouge; Sp ─ Gamba rosada) is one of the most exploited demersal resources in the Western Mediterranean Sea. However, information regarding the mating system and mate choice pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 65 publications
3
22
0
Order By: Relevance
“…Our mean observed and expected heterozygosities (H O = 0.468, H E = 0.633) were in accordance with recent studies using the same set of microsatellite loci (H O = 0.443, H E = 0.611 recalculated excluding Aa421 33 ; H O = 0.458, H E = 0.628 34 ). The mean number of alleles per locus and sample (N A = 9.1, Table 2) was slightly higher than reported previously with the same microsatellite loci (N A = 7.9 recalculated excluding Aa421 33 ; N A = 7.8 34 ), probably due to the sample size in our study almost doubling the one in those previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our mean observed and expected heterozygosities (H O = 0.468, H E = 0.633) were in accordance with recent studies using the same set of microsatellite loci (H O = 0.443, H E = 0.611 recalculated excluding Aa421 33 ; H O = 0.458, H E = 0.628 34 ). The mean number of alleles per locus and sample (N A = 9.1, Table 2) was slightly higher than reported previously with the same microsatellite loci (N A = 7.9 recalculated excluding Aa421 33 ; N A = 7.8 34 ), probably due to the sample size in our study almost doubling the one in those previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…There are some factors that could be responsible for these deviations from HWE genotypic proportions, such as inbreeding, null alleles or subpopulation structure. According to a recent study about the mating structure of A. antennatus, most of the mating individuals of the spawning groups are not related 33 , so we did not consider inbreeding to be the cause of the HWE disequilibrium found in our results. Null alleles could explain the heterozygote deficiency, according to our results showed by Micro-checker (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The heterozygote deficit, reflected in positive F IS values (average = 0.271; Table 1), was responsible for the observed HW deviations. We ruled out possible inbreeding, as a recent study suggested that spawning groups of this species are formed mostly by unrelated individuals 22 . We believe that this deficit may be due to the null alleles as previously observed for A. antennatus and other decapods 13,15 and in the case of WM, they could also be due to the Wahlund effect.…”
Section: Discussionmentioning
confidence: 99%
“…These molecular markers were distributed in three multiplex PCRs (sets of 3–5 loci) and one singleplex PCR for optimal amplification, following standard procedures with an annealing temperature of 50 °C or 60 °C, as described in Planella et al . 22 . PCR product sizing was performed with the GeneScan TM 500 LIZ ® size standard (Applied Biosystems) on an ABI PRISM ® 3130 Genetic Analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%